Biomathematical Model to Analyze the Transmission Dynamics of Covid-19: Case Study, Santiago de Cali, Colombia - Alfaro-Marchant, M; Vargas-Guzman, M (Public Library of Science, 2024)
The Covid-19 pandemic has challenged both the scientific community and government authorities in Colombia. Both sectors are collaborating to understand the transmission and spread of the virus and to establish control strategies. This study proposes a biomathematical model with difference equations to analyze the transmission of Covid-19 in Santiago de Cali from March 2020 to June 2022. The results indicate that most of the inhabitants could be positive at some point, but with containment measures, a manageable number of symptomatic cases could be maintained. In addition, the cumulative fatality curve is fitted to the Gompertz model. The method used for parameter fitting or estimation was Gauss-Newton. This approach provides valuable information for decision making and pandemic management in the city. © 2024 Alfaro et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.